1997
DOI: 10.1126/science.277.5331.1483
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology and Ecology of Filamentous Sulfur Formation

Abstract: A highly motile chemoautotrophic strain of hydrogen sulfide-oxidizing bacteria from coastal seawater produces solid sulfur filaments of dimensions 0.5 to 2.0 micrometers by 20 to 500 micrometers. Filamentous sulfur is rapidly produced by direct excretion by a vibrioid organism, and the newly produced filaments are thickened by the deposition of sulfur by other members of the population. Microscopic observations of the flocculent discharge material collected from diffuse-flow hydrothermal vents (gON, East Pacif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 13 publications
4
89
0
Order By: Relevance
“…7) (26). In addition to sox, the strains have both cytoplasmic and periplasmic sulfide-quinone oxidoreductases that catalyze the oxidation of sulfide to elemental sulfur, probably contributing to filamentous sulfur formation by deep-sea ventProteobacteria (27). Furthermore, consistent with our previous enzyme assay (28), strain NBC37-1 has two copies of sulfite: cytochrome c oxidoreductase (Sor).…”
Section: Resultssupporting
confidence: 72%
“…7) (26). In addition to sox, the strains have both cytoplasmic and periplasmic sulfide-quinone oxidoreductases that catalyze the oxidation of sulfide to elemental sulfur, probably contributing to filamentous sulfur formation by deep-sea ventProteobacteria (27). Furthermore, consistent with our previous enzyme assay (28), strain NBC37-1 has two copies of sulfite: cytochrome c oxidoreductase (Sor).…”
Section: Resultssupporting
confidence: 72%
“…Inspection of fresh collections of floc under a compound microscope revealed no filaments. Laboratory cultures of vibrioid organisms were induced to form similar accumulations of amorphous sulfur by flowing a steady stream of H 2 S into organic-rich soils (Taylor & Wirsen 1997). It is probable that disturbance of the bottom enhances the diffusion of H 2 S from deeper anoxic layers.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfur-oxidizing bacteria, which provide a base for the chemosynthetic food web in these deep sea environments, produce filamentous sulfur (Taylor and Wirsen, 1997). Laboratory Raman studies by Pasteris et al (2001) have identified elemental sulfur in the S 8 configuration in the bacteria Thioploca and Beggiatoa.…”
Section: Elemental Sulfurmentioning
confidence: 99%